1962
DOI: 10.3171/jns.1962.19.12.1038
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Hypertonic Mannitol Solution in Decreasing Brain Mass and Lowering Cerebrospinal-Fluid Pressure

Abstract: T HE value of a chemical or pharmacological agent that temporarily would lower cerebrospinal-fluid pressure and decrease the mass of the brain is apparent to neurosurgeons. Since Weed and 1VfcKibben 4e,47 demonstrated that various hypertonic solutions could accomplish these effects, many agents have been tested. 6,14,17,22,29,45,49,55 Each of these substances has been found to have certain disadvantages or toxic effects. The use of hypertonic urea for these purposes originally was proposed by Fremont-Smith and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(47 citation statements)
references
References 44 publications
0
45
0
2
Order By: Relevance
“…Further studies have suggested an additional role in reducing infarct size when used with hypothermia [50] and improved postischemic blood flow in animals pretreated with mannitol [51]. One of the first human studies using mannitol came in 1962 when Drs Wise and Chater [52] demonstrated mannitol as a safe and effective agent to decrease intracranial pressure. In 2003, Bereczki et al [53] performed a prospective observational study of 805 patients reviewing case fatality when mannitol was used in patients admitted within 72 hours of stroke onset.…”
Section: Pros and Cons Of Hyperosmolar Therapymentioning
confidence: 99%
“…Further studies have suggested an additional role in reducing infarct size when used with hypothermia [50] and improved postischemic blood flow in animals pretreated with mannitol [51]. One of the first human studies using mannitol came in 1962 when Drs Wise and Chater [52] demonstrated mannitol as a safe and effective agent to decrease intracranial pressure. In 2003, Bereczki et al [53] performed a prospective observational study of 805 patients reviewing case fatality when mannitol was used in patients admitted within 72 hours of stroke onset.…”
Section: Pros and Cons Of Hyperosmolar Therapymentioning
confidence: 99%
“…Mannitol, a metabolically inert hexose, is the beststudied osmotic agent, and is typically used first-line for osmotherapy in the United States. It has been consistently shown to reduce intracranial pressure (ICP) (1,2). However, there is currently growing interest in hypertonic saline as an alternative to mannitol (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Even in the presence of a disrupted BBB, an osmotic gradient is still established and mannitol is still able to reduce total brain volume (12,13). Hypertonic mannitol solutions rapidly draw water into the extracellular compartment increasing plasma volume (2), which transiently dilutes extracellular sodium (14)(15)(16). In the kidney, mannitol acts as an osmotic diuretic resulting in the excretion of large volumes of free water (2,17).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations